Role of therapeutic plasma exchange in acute liver failure due to yellow phosphorus poisoning - Varghese, Joy (Indian J Gastroenterol, 2021)
BACKGROUND: Therapeutic plasma exchange (TPE) has been utilized in various liver disorders. There is limited data on the efficacy of TPE in patients with acute liver failure (ALF). METHODS: Study group consisted of patients who underwent TPE for ALF due to yellow phosphorous poisoning (YPP) between 2015 and 2019. Demographic data and biochemical parameters were recorded before and after TPE. Overall survival and transplant-free survival (based on King’s College Hospital Criteria [KCHC]) were analyzed. RESULTS: Forty-three patients underwent TPE for ALF due to YPP. Most of them were young males. Overall survival was 34 (79.06%). In our study population, 20 patients fulfilled KCHC (Group A) and 23 did not fulfill KCHC (Group B). Both the groups showed significant improvement in alanine aminotransferase, aspartate aminotransferase, and international normalized ratio (INR) after TPE (p < 0.05). In Group B, there was significant improvement in ammonia after TPE (p < 0.05) and all 23 patients (100%) survived after TPE. In Group A, 4 underwent liver transplantation (LT), 7 survived without LT, and the remaining 9 died without LT. Mean survival after completing TPE was 41.2 ± 44.5 days in Group A and 90 days in Group B. This difference was statistically significant (p = 0.001). There was statistically significant difference in post-TPE values of INR (p = 0.012) and ammonia (p = 0.011) between non-survivors and survivors. Adverse events such as hypotension (11.62%) and minor allergic reaction (4.65%) were managed conservatively. CONCLUSION: TPE is an effective procedure in ALF due to YPP, not fulfilling KCHC for LT. In KCHC fulfilled group, though it shows LT-free survival benefit, there is requirement of prospective, large volume, multi-center study to assess its efficacy. [Image: see text]